Amorphous soft magnetic composite material and preparation method thereof

By using composite materials of FeSiBCCr amorphous powder, FeNi powder and manganese-zinc ferrite powder, and adopting steps such as passivation treatment, insulation coating treatment, warm press molding and annealing, the problem of amorphous soft magnetic composite materials under low pressure conditions is solved. It overcomes the problems of difficult molding and insufficient magnetic properties, and achieves the excellent characteristics of high magnetic permeability, low eddy current loss and high DC superposition.

CN118866496BActive Publication Date: 2025-01-21TDG HLDG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411333443.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-21
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing amorphous soft magnetic composite materials are difficult to form at high density under low pressure conditions, and the magnetic permeability and DC superposition characteristics are insufficient, and the eddy current loss is high.

Method used

A composite material of FeSiBCCr amorphous powder, FeNi powder and manganese-zinc ferrite powder is used to form an amorphous material with high magnetic permeability and low eddy current loss through passivation treatment, insulation coating treatment, warm pressing molding and annealing. Soft magnetic composite materials.

Benefits of technology

High-density molding of materials is achieved under low pressure conditions, improving magnetic permeability and DC superposition characteristics, and effectively suppressing eddy current losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118866496B_ABST
    Figure CN118866496B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of amorphous soft magnetic materials, and specifically relates to an amorphous soft magnetic composite material and a preparation method thereof, comprising the following steps: (1) placing FeSiBCCr amorphous powder in a suspension of manganese zinc ferrite and ethanol for passivation treatment to obtain passivated FeSiBCCr amorphous powder; (2) mixing FeNi powder and passivated FeSiBCCr amorphous powder in proportion and placing them in a mixed solution of organic silicone resin and ethanol for coating treatment, and obtaining a mixed powder after sufficient stirring and drying; (3) adding a lubricant to the mixed powder, mixing evenly, placing it in a mold, pressing it at temperature, and performing stress relief annealing to obtain an amorphous soft magnetic composite material with high magnetic permeability, high DC superposition and low loss characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials, and in particular relates to an amorphous soft magnetic composite material and a preparation method thereof. Background Art

[0002] With the advancement of chip vertical power supply technology, chip power modules are developing towards miniaturization and high current power supply requirements, which poses a severe challenge to the performance of soft magnetic materials used in inductors. Compared with traditional manganese-zinc ferrite and crystalline metal soft magnetic materials, amorphous soft magnetic composite materials are made of a variety of materials, which can complement each other's advantages and are conducive to achieving high saturation magnetic induction intensity, high magnetic permeability, low loss and high DC superposition characteristics, and can meet the application requirements of high frequency, miniaturization and integration of magnetic devices.

[0003] At present, the preparation process of iron-based amorphous alloy magnetic powder cores usually includes the steps of powder mixing, passivation treatment, coating treatment, pressing and annealing heat treatment. Among them, the coating treatment is an important link that determines the comprehensive performance of the magnetic powder core in order to achieve a good insulation effect between magnetic particles. However, common coating layers such as epoxy resin, phenolic resin, phosphate and other insulating coating materials are non-magnetic substances. The decrease in magnetic permeability and saturation magnetic induction intensity caused by the magnetic dilution effect is the main problem they face. The patent with publication number CN117542648A discloses a method for preparing a high-density amorphous powder core, which uses phosphoric acid to coat amorphous magnetic powder. The magnetic powder core obtained after warm pressing has a high loss of more than 250mW / cm 3 . In addition, amorphous alloys have high hardness and are difficult to form under low pressure. There are large air gaps between powders, which makes it easier to reach magnetic saturation, accelerate the rate of magnetic permeability decrease, and deteriorate DC superposition performance. Excessive pressure can easily lead to rupture of the insulation layer, increase the stress in the magnetic powder core, and increase the loss. The patent with publication number CN107967976A discloses a method for preparing an amorphous magnetic powder core, in which amorphous powder coated with ferrite and adhesive is heated at room temperature to 18t / cm 3 The amorphous magnetic powder core is obtained by pressing under a pressure of . Due to the high pressure during pressing, the loss is high at 50kHz and 0.1T, which is 711mW / cm 3 Therefore, it is very necessary to develop an amorphous soft magnetic composite material that can be formed at a high density under low pressure and has the excellent properties of high magnetic permeability, low eddy current loss and high DC superposition. Summary of the invention

[0004] In order to solve the above problems, the purpose of the present invention is to provide an amorphous soft magnetic composite material and a preparation method thereof, which can be formed under low pressure conditions, improve the magnetic permeability and DC superposition characteristics, and effectively suppress eddy current loss, and adopt the following technical solutions:

[0005] An amorphous soft magnetic composite material mainly comprises FeSiBCCr amorphous powder, FeNi powder and manganese-zinc ferrite powder, wherein the particle size of the FeSiBCCr amorphous powder is 10-20 μm, the particle size of the FeNi powder is 1-10 μm, and the particle size of the manganese-zinc ferrite powder is 0.5-5 μm;

[0006] Among them, the FeSiBCCr amorphous powder is placed in a suspension of manganese zinc ferrite powder and ethanol for passivation treatment, and the total mass of the FeSiBCCr amorphous powder and the manganese zinc ferrite powder is used as the calculation basis, the manganese zinc ferrite powder accounts for 0.5-3wt%, and the ethanol accounts for 5-10wt%;

[0007] The total mass of FeNi powder and passivated FeSiBCCr amorphous powder is used as the calculation basis; the mass proportion of passivated FeSiBCCr amorphous powder is 50-80wt%, and the mass proportion of FeNi powder is 20-50wt%;

[0008] Among them, FeNi powder and passivated FeSiBCCr amorphous powder need to be mixed, and then coated, warm pressed and annealed to obtain an amorphous soft magnetic composite material;

[0009] The temperature of the warm pressing treatment is 180-230°C, the time of the warm pressing treatment is 10-60s, and the pressing pressure is 300-700MPa.

[0010] Preferably, the FeSiBCCr amorphous powder has a composition of Fe 73 Si 10 B 10 C 5 Cr 2 .

[0011] Preferably, the particle size of the FeSiBCCr amorphous powder is 12-17 μm, the particle size of the FeNi powder is 3-8 μm, and the particle size of the manganese-zinc ferrite powder is 1-3 μm;

[0012] Preferably, the particle size of the FeSiBCCr amorphous powder is 13-15 μm, the particle size of the FeNi powder is 5-7 μm, and the particle size of the manganese-zinc ferrite powder is 1.5-2.5 μm.

[0013] Preferably, the FeSiBCCr amorphous powder needs to be placed in a suspension of manganese zinc ferrite and ethanol for passivation treatment, and the total mass of the FeSiBCCr amorphous powder and the manganese zinc ferrite powder is used as the calculation basis, the mass proportion of the manganese zinc ferrite powder is 1-2.5wt%, and the mass proportion of the ethanol is 6-9wt%;

[0014] Preferably, the FeSiBCCr amorphous powder needs to be placed in a suspension of manganese zinc ferrite and ethanol for passivation treatment. The total mass of the FeSiBCCr amorphous powder and the manganese zinc ferrite powder is used as the calculation basis, the mass proportion of the manganese zinc ferrite powder is 1.5-2wt%, and the mass proportion of ethanol is 7-8wt%.

[0015] Preferably, the temperature of the warm-pressing treatment is 200-220°C, the time of the warm-pressing treatment is 20-50s, and the pressing pressure is 400-600MPa;

[0016] Preferably, the temperature of the warm-pressing treatment is 205-215° C., the time of the warm-pressing treatment is 30-40 seconds, and the pressing pressure is 450-550 MPa.

[0017] The method for preparing the above-mentioned amorphous soft magnetic composite material comprises the following steps:

[0018] (1) placing FeSiBCCr amorphous powder in a suspension of manganese zinc ferrite powder and ethanol for passivation treatment to obtain passivated FeSiBCCr amorphous powder;

[0019] (2) mixing the passivated FeSiBCCr amorphous powder and FeNi powder and placing them in a mixed solution of silicone resin and organic solvent for insulation coating treatment, and then fully stirring and drying to obtain a mixed powder;

[0020] (3) Adding a lubricant to the mixed powder, mixing well, putting it into a mold, pressing it at a temperature, and annealing it to obtain an amorphous soft magnetic composite material.

[0021] Preferably, in step 2, the total mass of the FeNi powder and the passivated FeSiBCCr amorphous powder is used as the calculation basis, the mass of the silicone resin accounts for 2-5wt%, and the organic solvent is ethanol, and the mass of the ethanol used accounts for 5-10wt%;

[0022] Preferably, in step 2, the total mass of the FeNi powder and the passivated FeSiBCCr amorphous powder is used as the calculation basis, the mass of the silicone resin accounts for 3-4wt%, the organic solvent is ethanol, and the mass of the ethanol used accounts for 7-9wt%.

[0023] Preferably, in step 3, the lubricant is barium stearate, and the amount of the lubricant is 0.2-0.4wt% of the mass of the mixed powder;

[0024] Preferably, in step 3, the lubricant is barium stearate, and the amount of the lubricant is 0.25-0.35 wt % of the mass of the mixed powder.

[0025] Preferably, in step 3, the annealing temperature is 350-450°C, the holding time is 50-150min, the heating rate is 8-12°C / min, and the furnace is cooled;

[0026] Preferably, in step 3, the annealing temperature is 380-420° C., the holding time is 80-120 min, the heating rate is 9-10° C. / min, and the furnace is cooled.

[0027] The present invention has the following beneficial effects:

[0028] The manganese-zinc ferrite powder insulation coating material used in the present invention has high resistivity and high magnetic permeability. When coated on the surface of amorphous powder, it can improve the magnetic permeability of amorphous soft magnetic composite materials and reduce eddy current losses.

[0029] In the preparation method of the amorphous soft magnetic composite material provided by the present invention, a warm pressing process is used to improve the fluidity between powders and reduce the internal stress of material pressing; while forming under low pressure conditions, the density of the material is also improved, thereby achieving the purpose of improving the magnetic permeability;

[0030] The present invention adds FeNi powder with small particle size to the amorphous soft magnetic composite material, wherein the FeNi powder has good plasticity and has a good molding effect during the pressing process, and can make up for the disadvantage of poor molding ability of the amorphous powder. In addition, the FeNi powder with small particle size can fill the pores between the amorphous powders, thereby improving the density of the composite material, enhancing the coupling effect between the magnetic particles, and further improving the magnetic permeability of the composite material and reducing the magnetic loss; in addition, the FeNi powder fills the gaps between the amorphous powders to form discrete distributed air gaps, delaying magnetic saturation and improving the DC superposition performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a graph showing the relationship between the magnetic permeability and the frequency of Examples 1-4 and Comparative Examples 1-4;

[0032] Figure 2 This is a graph showing the relationship between the loss and frequency of Examples 1-4 and Comparative Examples 1-4 under the 20mT test condition;

[0033] Figure 3 The loss diagram of Examples 1-4 and Comparative Examples 1-4 under 100mT, 50kHz test conditions;

[0034] Figure 4 This is a loss diagram of Examples 1-4 and Comparative Examples 1-4 under 50mT, 100kHz test conditions. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the amorphous soft magnetic composite material and the preparation method thereof provided by the present invention are further described in detail through the following examples in combination with the accompanying drawings.

[0036] The present invention sets embodiments 1-4 to provide an amorphous soft magnetic composite material, which mainly includes FeSiBCCr amorphous powder with a particle size of 10-20 μm, FeNi powder with a particle size of 1-10 μm and manganese zinc ferrite powder with a particle size of 0.5-5 μm; the FeSiBCCr amorphous powder is placed in a suspension of manganese zinc ferrite powder and ethanol for passivation treatment, and the masses of the FeNi powder and the passivated FeSiBCCr amorphous powder are shown in Table 1.

[0037] Table 1 shows the powder quality of Examples 1-4

[0038]

[0039] Example 1 is as follows:

[0040] The present invention provides an amorphous soft magnetic composite material, the preparation method of which comprises the following specific steps:

[0041] (1) Weighing 99.5 g of FeSiBCCr amorphous powder and placing it in a suspension of 0.5 g of manganese-zinc ferrite powder and 7 g of ethanol for passivation treatment to obtain passivated FeSiBCCr amorphous powder;

[0042] (2) mixing the passivated FeSiBCCr amorphous powder and FeNi powder in the proportions shown in Table 1 to obtain a mixed powder;

[0043] (3) The mixed powder is placed in a mixed solution of silicone resin and ethanol for insulation coating treatment, wherein the silicone resin used for the insulation coating treatment accounts for 3wt% of the total mass of the mixed powder, and the ethanol accounts for 8wt% of the total mass of the mixed powder. The mixed powder is fully stirred and dried; barium stearate is added to account for 0.3wt% of the total mass of the mixed powder, and the mixture is pressurized at 200°C and 550MPa for 30s to obtain a ring-shaped material with an outer diameter of 14mm and an inner diameter of 8mm; the material is subjected to stress relief annealing treatment at 450°C for 120min to obtain an amorphous soft magnetic composite material.

[0044] Example 2 is as follows:

[0045] The present invention provides an amorphous soft magnetic composite material, the preparation method of which comprises the following specific steps:

[0046] (1) Weighing 98 g of FeSiBCCr amorphous powder and placing it in a suspension of 2 g of manganese zinc ferrite powder and 8 g of ethanol for passivation treatment to obtain passivated FeSiBCCr amorphous powder;

[0047] (2) mixing the passivated FeSiBCCr amorphous powder and FeNi powder in the proportions shown in Table 1 to obtain a mixed powder;

[0048] (3) The mixed powder is placed in a mixed solution of silicone resin and ethanol for insulation coating treatment, wherein the silicone resin used for the insulation coating treatment accounts for 1wt% of the total mass of the mixed powder, and the ethanol accounts for 10wt% of the total mass of the mixed powder. The mixed powder is fully stirred and dried; barium stearate is added to account for 0.4wt% of the total mass of the mixed powder, and the mixture is pressurized at 700MPa for 20s at a temperature of 220°C to obtain a ring-shaped material with an outer diameter of 14mm and an inner diameter of 8mm; the material is subjected to stress relief annealing treatment at 350°C for 60min to obtain an amorphous soft magnetic composite material.

[0049] Example 3 is as follows:

[0050] The present invention provides an amorphous soft magnetic composite material, the preparation method of which comprises the following specific steps:

[0051] (1) Weighing 99 g of FeSiBCCr amorphous powder and placing it in a suspension of 1 g of manganese zinc ferrite powder and 6 g of ethanol for passivation treatment to obtain passivated FeSiBCCr amorphous powder;

[0052] (2) mixing the passivated FeSiBCCr amorphous powder and FeNi powder in the proportions shown in Table 1 to obtain a mixed powder;

[0053] (3) The mixed powder is placed in a mixed solution of silicone resin and ethanol for insulation coating treatment, wherein the silicone resin used for the insulation coating treatment accounts for 2wt% of the total mass of the mixed powder, and the ethanol accounts for 12wt% of the total mass of the mixed powder. The mixed powder is fully stirred and dried; barium stearate is added to account for 0.2wt% of the total mass of the mixed powder, and the mixture is pressurized at 180°C and 700MPa for 15s to obtain a ring-shaped material with an outer diameter of 14mm and an inner diameter of 8mm; the material is subjected to stress relief annealing treatment at 300°C for 80min to obtain an amorphous soft magnetic composite material.

[0054] Embodiment 4 is as follows:

[0055] The present invention provides an amorphous soft magnetic composite material, the preparation method of which comprises the following specific steps:

[0056] (1) Weighing 97 g of FeSiBCCr amorphous powder and placing it in a suspension of 3 g of manganese zinc ferrite powder and 10 g of ethanol for passivation treatment to obtain passivated FeSiBCCr amorphous powder;

[0057] (2) mixing the passivated FeSiBCCr amorphous powder and FeNi powder in the proportions shown in Table 1 to obtain a mixed powder;

[0058] (3) The mixed powder is placed in a mixed solution of silicone resin and ethanol for insulation coating treatment, wherein the silicone resin used for the insulation coating treatment accounts for 4wt% of the total mass of the mixed powder, and the ethanol accounts for 6wt% of the total mass of the mixed powder. The mixed powder is fully stirred and dried; barium stearate is added to account for 0.25wt% of the total mass of the mixed powder, and the mixture is pressurized at 150°C and 350MPa for 40s to obtain a ring-shaped material with an outer diameter of 14mm and an inner diameter of 8mm; the material is subjected to stress relief annealing treatment at 400°C for 140min to obtain an amorphous soft magnetic composite material.

[0059] Comparative Example 1 is as follows:

[0060] The difference between this comparative example and Example 1 is that the pressing temperature is 25°C.

[0061] Comparative Example 2 is as follows:

[0062] An amorphous composite material, the preparation method comprises the following specific steps:

[0063] (1) 80 g of FeSiBCCr amorphous powder and 20 g of FeNi powder were mixed to form a mixed powder, which was placed in a mixed solution of silicone resin and ethanol for insulation coating treatment. The silicone resin used for the insulation coating treatment accounted for 4 wt% of the total mass of the mixed powder, and the ethanol accounted for 6 wt% of the total mass of the mixed powder. The mixed powder was fully stirred and dried;

[0064] (2) The added barium stearate accounts for 0.25wt% of the total mass of the mixed powder, and the pressure is maintained at 350MPa for 40s at a temperature of 150°C to obtain a ring-shaped material with an outer diameter of 14mm and an inner diameter of 8mm;

[0065] (3) The above material was subjected to stress relief annealing treatment at 400°C for 140 minutes to obtain an amorphous composite material.

[0066] Comparative Example 3 is as follows:

[0067] The difference between this comparative example and Example 2 is that the finished powder is not doped with FeNi powder.

[0068] Comparative Example 4 is as follows:

[0069] An amorphous material, the preparation method comprises the following specific steps:

[0070] (1) 100 g of FeSiBCCr amorphous powder was placed in a mixed solution of silicone resin and ethanol for insulation coating treatment, wherein the silicone resin used for insulation coating treatment accounted for 3 wt% of the total mass of the amorphous powder, and the ethanol accounted for 10 wt% of the total mass of the amorphous powder, and the mixture was fully stirred and dried;

[0071] (2) The added barium stearate accounts for 0.4 wt% of the total mass of the amorphous powder, and the pressure is maintained at 1200 MPa for 10 seconds at a temperature of 25°C to obtain a ring-shaped material with an outer diameter of 14 mm and an inner diameter of 8 mm;

[0072] (3) The above material is subjected to stress relief annealing treatment at 480°C for 120 minutes to obtain an amorphous material.

[0073] Comparing Example 1 with Comparative Example 1, it can be found that the performance of the amorphous composite material can be significantly improved by increasing the pressing temperature and the ferrite coating process, the effective magnetic permeability is increased, and the magnetic loss is reduced.

[0074] The changes in effective magnetic permeability and frequency between Examples 1-4 and Comparative Examples 1-4 were detected, and the results are as follows: Figure 1 As shown, in the range of 100-1000kHz, the effective magnetic permeability of the embodiment is significantly higher than that of the comparative example; the changes in magnetic loss and frequency of the embodiments 1-4 and the comparative examples 1-4 under the test condition of 20mT were detected, and the results are as follows Figure 2 As shown in FIG. 1 , the magnetic loss of the embodiment and the comparative example increases with the increase of frequency, and the magnetic loss of the embodiment is significantly lower than that of the comparative example. The magnetic loss of the embodiment 1-4 and the comparative example 1-4 under the test conditions of 100 mT and 50 kHz is detected. Figure 3 As shown, the magnetic loss of the embodiment is significantly lower than that of the comparative example; the loss of the embodiment 1-4 and the comparative example 1-4 under the test conditions of 50mT and 100kHz was detected. Figure 4 As shown, the magnetic loss of the embodiment is significantly lower than that of the comparative example; the DC superposition performance of embodiments 1-4 and comparative examples 1-4 was detected when the DC bias magnetic field was 100Oe. The results are shown in Table 2. The DC superposition ability of the magnetic permeability of the embodiment is maintained above 90%.

[0075] Table 2 shows the DC superposition performance results of the embodiments and comparative examples.

[0076]

[0077] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above descriptions are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An amorphous soft magnetic composite material, characterized in that: The material mainly includes FeSiBCCr amorphous powder, FeNi powder and manganese-zinc ferrite powder, the particle size of the FeSiBCCr amorphous powder is 10-20 μm, the particle size of the FeNi powder is 1-10 μm, and the particle size of the manganese-zinc ferrite powder is 0.5-5 μm; Among them, the FeSiBCCr amorphous powder is placed in a suspension of manganese zinc ferrite powder and ethanol for passivation treatment, and the total mass of the FeSiBCCr amorphous powder and the manganese zinc ferrite powder is used as the calculation basis, the manganese zinc ferrite powder accounts for 0.5-3wt%, and the ethanol accounts for 5-10wt%; The total mass of FeNi powder and passivated FeSiBCCr amorphous powder is used as the calculation basis, the mass proportion of passivated FeSiBCCr amorphous powder is 50-80wt%, and the mass proportion of FeNi powder is 20-50wt%; Among them, FeNi powder and passivated FeSiBCCr amorphous powder are mixed and placed in a mixed solution of silicone resin and organic solvent for insulation coating treatment. The total mass of FeNi powder and passivated FeSiBCCr amorphous powder is used as the calculation basis, the mass proportion of silicone resin is 2-5wt%, the organic solvent is ethanol, and the mass proportion of ethanol used is 5-10wt%; The mixed powder after the insulation coating treatment is fully stirred and dried, and then the amorphous soft magnetic composite material is obtained by warm pressing and annealing. The temperature of the warm pressing treatment is 180-230°C, the time of the warm pressing treatment is 10-60s, and the pressing pressure is 300-700MPa.

2. The amorphous soft magnetic composite material according to claim 1, characterized in that: The FeSiBCCr amorphous powder is composed of Fe 73 Si 10 B 10 C5Cr2.

3. The amorphous soft magnetic composite material according to claim 1, characterized in that: The particle size of the FeSiBCCr amorphous powder is 12-17 μm, the particle size of the FeNi powder is 3-8 μm, and the particle size of the manganese-zinc ferrite powder is 1-3 μm.

4. The amorphous soft magnetic composite material according to claim 1, characterized in that: The FeSiBCCr amorphous powder needs to be placed in a suspension of manganese zinc ferrite and ethanol for passivation treatment. The total mass of the FeSiBCCr amorphous powder and the manganese zinc ferrite powder is used as the calculation basis, the mass proportion of the manganese zinc ferrite powder is 1-2.5wt%, and the mass proportion of ethanol is 6-9wt%.

5. The amorphous soft magnetic composite material according to claim 1, characterized in that: The temperature of the warm-pressing treatment is 200-220° C., the time of the warm-pressing treatment is 20-50 seconds, and the pressing pressure is 400-600 MPa.

6. The amorphous soft magnetic composite material according to claim 1, characterized in that: The temperature of the warm-pressing treatment is 205-215° C., the time of the warm-pressing treatment is 30-40 seconds, and the pressing pressure is 450-550 MPa.

7. A method for preparing an amorphous soft magnetic composite material according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: placing FeSiBCCr amorphous powder in a suspension of manganese zinc ferrite powder and ethanol for passivation treatment to obtain passivated FeSiBCCr amorphous powder; Step 2: The passivated FeSiBCCr amorphous powder and FeNi powder are mixed and placed in a mixed solution of silicone resin and organic solvent for insulation coating treatment, and then fully stirred and dried to obtain a mixed powder; Step 3: Add lubricant to the mixed powder, mix well and put it into a mold, press it at warm temperature, and after annealing, obtain an amorphous soft magnetic composite material.

8. The method for preparing an amorphous soft magnetic composite material according to claim 7, characterized in that: In step 3, the lubricant is barium stearate, and the amount of the lubricant is 0.2-0.4wt% of the mass of the mixed powder.

9. The method for preparing an amorphous soft magnetic composite material according to claim 7, characterized in that: In the step 3, the annealing temperature is 350-450° C., the holding time is 50-150 min, the heating rate is 8-12° C. / min, and the furnace is cooled.

Citation Information

Patent Citations

  • High-density amorphous powder core inductor and preparation method thereof

    CN117542648A

  • Amorphous magnetic powder core precursor particle, amorphous magnetic powder core and preparation method thereof

    CN107967976A

  • High-permeability low-loss iron-based amorphous composite magnetic powder core and preparation method thereof

    CN117497278A

  • High-permeability low-loss nanocrystalline composite magnetic powder core and preparation method thereof

    CN117936217A